Maxwell's enduring legacy : a scientific history of the Cavendish Laboratory - Longair, Malcolm S., 1941- (2016)
"The Cavendish Laboratory is arguably the most famous physics laboratory in the world. Founded in 1874, it rapidly gained a leading international reputation through the researches of the Cavendish professors beginning with Maxwell, Rayleigh, J.J. Thomson, Rutherford and Bragg. Its name will always be associated with the discoveries of the electron, the neutron, the structure of the DNA molecule and pulsars, but these are simply the tip of the iceberg of outstanding science. The physics carried out in the laboratory is the central theme of the book and this is explained in reasonably non-technical terms. The research activities are set in their international context. Generously illustrated, with many pictures of the apparatus used and diagrams from the original papers, the story is brought right up to date with descriptions of the science carried out under the leadership of the very different personalities of Mott, Pippard and Edwards."--Page 4 of cover.
Part I. To 1874. Physics in the nineteenth century -- Mathematics and physics in Cambridge in the nineteenth century -- Part II. 1874 to 1879. The Maxwell era -- Part III. 1879 to 1884. Rayleigh's quinquennium -- Part IV. 1884 to 1919. The challenges facing J.J. Thomson -- The Thomson era, 1884-1900 : the electron -- The Thomson era, 1900-1919 : atomic structure -- Part V. 1919 to 1937. Rutherford at McGill and Manchester universities : new challenges in Cambridge -- The Rutherford era : the radioactivists -- The Rutherford era : the seeds of the new physics -- Part VI. 1938 to 1953. Bragg and the war years -- Bragg and the post-war years -- Part VII. 1953 to 1971. The Mott era : an epoch of expansion -- The Mott era : radio astronomy and high-energy physics -- The Mott era : the growth of condensed matter physics -- Part VIII. 1971 to 1982. The Pippard era : a new Laboratory and a new vision -- The Pippard era : radio astronomy, high-energy physics and laboratory astrophysics -- The Pippard era : condensed matter physics -- Part IX. 1984 to 1995. The Edwards era : a new epoch of expansion -- The Edwards era : new directions in condensed matter physics -- The Edwards era : high-energy physics and radio astronomy -- Part X. 1995 to present. Towards the new millennium and beyond -- Appendix : the evolution of the new museums site.
Includes bibliographical references (pages 589-639) and indexes.
Keywords: Cavendish Laboratory (Cambridge, England) -- History; Cavendish Laboratory (Cambridge, England); Cavendish Laboratory; Maxwell; History